DEVELOPMENT OF SELECTED CAPITA BOOK OF MATHEMATICS BASED ON MEANINGFUL LEARNING FOR PROSPECTIVE MATHEMATICS TEACHER - dwi ivayana sari; moh zayyadi (FKIP Universitas Muhammadiyah Tangerang, 2026)
This study aimed to design, develop, and feasibility test of selected capita book of mathematics based on meaningful learning for prospective mathematics teachers. This research was a Research and Development (R&D). The development model in this study was Four-D model by Thiagarajan, Semmel and Semmel. The stages in this development were define, design, develop and disseminate. The subjects of this study were prospective 6th semester mathematics teacher at STKIP PGRI Bangkalan, East Java, Indonesia. This study used validity, practicality and effectiveness tests. The instruments in this study included validation sheets, lecturer and prospective mathematics teacher response questionnaires, observation sheets on lecturer' abilities in managing learning, observation sheets on prospective mathematics teacher activities, and test questions. The analysis technique in this study used descriptive statistics in the form of averages and percentages. The results of development of selected capita book of mathematics based on meaningful learning met valid, practical and effective categories. This book was a pedagogical tool that supports prospective mathematics teachers in building connections between mathematical concepts and their applications in learning contexts.